THE CONCEPT OF PSYCHOLINGUISTIC CONDITIONING AND ITS PLACE IN LINGUISTICS - Islomov Dilshod Shomurodovich (Western European Studies, 2026)
In this article, the scientific views and opinions of the world linguists about the concept of psycholinguistic conditioning are presented and the reaction to them is expressed through analysis. In addition, special importance was given to the place of the concept of psycholinguistic conditioning in linguists. At the same time, it was shown in the analytical part of the article that psycholinguistic conditioning is one of the important directions of modern linguistics and its interrelationship with cognitive linguistics, applied linguistics, sociolinguistics, psycholinguistics, neuropsycholinguistics
Keywords: psycholinguistic conditioning; linguistics; psycholinguistics; neuropsycholinistics